Assessment of the inter-lap stability and relationship between the race time and start, clean swim, turn and finish variables in elite male junior swimmers' 200 m freestyle - Morais, J. E.; Barbosa, T. M.; Forte, P.; Pinto, J. N.; Marinho, D. A. (Sports Biomechanics, 2021)
The aims of this study were to: (1) assess the stability (mean and normative) of the lap performance, and a set of clean swim and turn variables of junior male swimmers in the 200 m freestyle, and; (2) verify the relationship between the start, clean swim, turn, and finish phases in the 200 m freestyle. Seventy-six individual races in the 200 m freestyle at the 2019 long-course LEN European Junior Championships were analysed. Start, clean swim, turn, and finish variables were assessed. The lap performance showed a significant variance. The highest variation was verified between the first and third lap (Coefficient of Variation=7.37%). The clean swim and the total turn also presented a significant variance. Normative stability indicated a moderate to very-high stability for all variables. All phases of the race had significant correlations with the final race time (p<0.001). The total turn (i.e., the total time spent to perform the turn), specifically turn #3, showed the largest correlation with the total race performance. The significant correlation between all phases of the race and the final race time indicates that coaches and swimmers should customise the swimmers' preparation and race strategy at major international competitions, based on the individual characteristics of each swimmer.